Accelerating access and scale-up of optimized antiretroviral therapy in low-income and middle-income countries: results of a coordinated end-to-end approach. (15th December 2021) - Harris, Emily Lark; Blumer, Katherine; Perez Casas, Carmen; Ferris, Danielle; Amole, Carolyn; Doherty, Meg; Auton, Martin
Abstract : N/A: The global HIV community invested in multiple, high-profile partnerships and shepherded unprecedented political support to expedite the transition to dolutegravir (DTG)-based regimens. The goal? To accelerate access to simpler, safer, more robust, and more affordable HIV treatment by harnessing the collective power of scientists, regulators, drug companies, donors, implementers, advocates, and people with HIV (PWH). The inspiration? End-to-end approaches to introducing new products that mitigate risk and encourage early planning and resource allocation for all aspects of product introduction and preparation for scale-up. This approach of planning with the 'end-in-mind' – and the belief that this end-to-end mindset can facilitate healthy markets, catalyze the application of new health technologies, and accelerate the development of improved products – is increasingly being applied across HIV prevention, care, and treatment (e.g. for biomedical prevention), and across health sectors (e.g. in maternal and child health, food security and water, and sanitation). This review of antiretroviral treatment (ART) optimization efforts from 2015 through 2020 discusses what worked, what is next, and how the learnings from HIV treatment can inform the broader global health community looking for innovative partnership models to accelerate adoption and enable scale-up of promising new products and programs.